2014
DOI: 10.21608/ejar.2014.156436
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatments and Drying Temperatures on the Quality of Dried Pleurotus Mushroom Spp.

Abstract: This study was carried out to evaluate the effect of pretreatments prior drying as well as drying temperature on quality of the dried mushroom. Rehydration ratio and color of the dried product are the most effective parameter for judging and evaluating the drying process. Pleurotus ostreatus and Pleurotus eryngii samples were pretreated by different solutions (NaCl, citric acid and sodium metabisulfite) at room temperature and at 96± 2 o C. Pretreated and control mushroom samples were dried by hot air at 50, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Maray et al [22] revealed that blanching at 90 o C for 3 min and immersing in a 0.5% citric acid for 30 min lowered the BI of dried oyster mushrooms (Pleurotus ostreatus). The result from this study was in agreement with the findings of Hassan and Medany [23], who showed that dried Pleurotus ostreatus and Pleurotus eryngii steeped in 0.1% Na2S2O5, 0.1% NaCl, and 0.1% citric acid for 10 min had lower BI than that of untreated mushrooms. Lower BI in blanched, NaCl, and citric acid-treated mushrooms can probably be related to inactivation of browning enzymatic reactions.…”
Section: Effect Of Different Pretreatments On Ppo Activity and Browni...supporting
confidence: 92%
“…Maray et al [22] revealed that blanching at 90 o C for 3 min and immersing in a 0.5% citric acid for 30 min lowered the BI of dried oyster mushrooms (Pleurotus ostreatus). The result from this study was in agreement with the findings of Hassan and Medany [23], who showed that dried Pleurotus ostreatus and Pleurotus eryngii steeped in 0.1% Na2S2O5, 0.1% NaCl, and 0.1% citric acid for 10 min had lower BI than that of untreated mushrooms. Lower BI in blanched, NaCl, and citric acid-treated mushrooms can probably be related to inactivation of browning enzymatic reactions.…”
Section: Effect Of Different Pretreatments On Ppo Activity and Browni...supporting
confidence: 92%
“…Likewise, protein content of P. tuoliensis stored at 4 °C decreased with increasing of storage time (Li et al, 2021). In general, the drying process causes a significant reduction in protein content of mushrooms (Hassan and Medany, 2014). The lowest protein content in P. eryngii was found in microwave drying among different drying methods (Lüle, 2014), which was consistent with our findings.…”
Section: P Ostreatussupporting
confidence: 89%
“…According to Nöfer et al (2018), prolonged drying time and high temperatures may degrade the mushroom aroma. According to Hassan and Medany (2014), pre-treatment of P. ostreatus and P. eryngii with 0.1% sodium metabisulfite at room temperature improved mushroom color and microbiological characteristics, while also retaining its nutrients. The highest rehydration ratio was found in the untreated mushrooms.…”
Section: Pre-treatments Before Dryingmentioning
confidence: 99%
“…Additionally, soaking mushrooms in 0.1% NaCl or 0.1% citric acid for 10 min at room temperature produced acceptable results, though they were not as good as those treated with sodium metabisulfite. Hassan and Medany (2014) found out blanching as a pre-treatment is ineffective for enhancing the quality of dried mushrooms. Not just them, Argyropoulos et al (2011b) in the research concluded that blanching can cause undesired color and texture of mushrooms (hardens), while also inhibiting enzyme activity and reducing microbial populations.…”
Section: Pre-treatments Before Dryingmentioning
confidence: 99%